2019
DOI: 10.1109/tap.2019.2908109
|View full text |Cite
|
Sign up to set email alerts
|

$8\times8\,\,Ka$ -Band Dual-Polarized Array Antenna Based on Gap Waveguide Technology

Abstract: This paper describes an 8×8 fully-metallic highefficiency dual-polarized array antenna working at Ka-band, based on Gap Waveguide concept. The radiating element is a circular aperture backed by two stacked cylindrical cavities, which are fed orthogonally to achieve a dual-polarized performance. Both feeding layers consist of a gap waveguide corporate network to reach all the cavities backing each radiating element. Cavities are naturally integrated within the bed of nails hosting grooves and ridges for guiding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 26 publications
(26 reference statements)
0
35
0
Order By: Relevance
“…This has been done on purpose. Measurements in [8] revealed that the phase difference in broadside direction between V-Pol and H-Pol field components was of −140 • at the central frequency (30.25 GHz). However right-hand CP (RHCP) would need −90 • phase difference instead.…”
Section: Coupler Modification For Cp Conversionmentioning
confidence: 99%
See 4 more Smart Citations
“…This has been done on purpose. Measurements in [8] revealed that the phase difference in broadside direction between V-Pol and H-Pol field components was of −140 • at the central frequency (30.25 GHz). However right-hand CP (RHCP) would need −90 • phase difference instead.…”
Section: Coupler Modification For Cp Conversionmentioning
confidence: 99%
“…The first of these pieces hosts a novel Riblet-type coupler implemented in GW. The remaining three pieces that make up the antenna are, in ascending order, the feeding, coupling and radiation layers, which were previously presented in [8].…”
Section: Riblet-type Coupler Designmentioning
confidence: 99%
See 3 more Smart Citations